The High Subarctic Forest-Tundra of Northwestern Canada: Position, Width, and Vegetation Gradients in Relation to Climate - Timoney, K.P.; La Roi, G.H.; Zoltai, S.C.; Robinson, A.L. (ARCTIC, 1992)
A phytogeoclimatic study of the high subarctic region of Canada between Hudson Bay and the Cordillera at the northern Yukon-Mackenzie border was undertaken to provide a verifiable and quantitative synthesis of forest-tundra vegetation ecology. Three field seasons of vegetation and terrain studies provided ground truth for a grid of 1314 black-and-white air photos that cover ca. 24% of the forest-tundra and adjacent low Subarctic and low Arctic. Air photos were analyzed for percentage cover of nine vegetation-terrain types, bedrock and parent materials, landforms, and elevations. The forest-tundra, as bounded by the 1000:1 and 1:1000 tree:upland tundra cover isolines, spans an average 145 ± 72 km (median 131 km) and increases in width from northwest to southeast. The transition from 10:1 to 1:10 tree:upland tundra cover occupies one-fourth to one-half the area of the forest-tundra. Regional slope of the land probably accounts for much of the variation in width of the forest-tundra. Southern outliers of forest-tundra in the northwest are found mainly in areas of high elevation. Across much of the northwest, steep vegetation gradients occur near the northern limit of trees. North of Great Slave Lake, steep vegetation gradients shift from the northern to the southern half of the forest-tundra and maintain this position eastward to Hudson Bay. The forest-tundra of the northwest receives roughly three-fourths the mean annual net radiation available to the southeast and central districts.Key words: air photos, boreal, climate, ecology, forest-tundra, high Subarctic, Northwest Territories, plant geography, tree line, vegetation On a entrepris une étude phytogéoclimatique de la zone de l’Extrême-Subarctique canadien comprise entre la baie d’Hudson et la cordillère, située à la frontière du Yukon-Mackenzie, en vue d’offrir une synthkse vérifiable et quantitative de l’écologie végétale de la forêt-toundra. Trois saisons d’étude de végétation et de terrain ont fourni des données de verification pour une grille de 1314 ...